Examining Risk Factors and Protective Resources as Predictors of Recovery Among Youth With Mental Illness and Lived Experience of Homelessness. Issue 5 (July 2023) - Manoni-Millar, Stéphanie; Distasio, Jino; Latimer, Eric; Somers, Julian; Stergiopoulos, Vicky; Kerman, Nick; Roy, Laurence; Aubry, Tim
High level of mental health problems are a critical concern among youth experiencing or at-risk of homelessness. Using data from a randomized controlled trial on Housing First in Canada, this study examined the risk factors and protective resources associated with mental health recovery among 215 homeless youth with mental illness at baseline and at a 24-month follow-up. At study entry, higher levels of recovery were associated with a lower number of adverse childhood experiences, less frequent presence of mental health symptoms, higher level of satisfaction with social relationships, and a higher level of psychological integration at baseline. At 24-months, a lower frequency of experiencing mental health symptoms and a higher level of psychological integration were associated with a higher level of recovery. The study's findings highlight the importance of protective resources, notably having supportive social relationships and a sense of belonging in the community as contributors to mental health recovery